O processo de ensinar na educação infantil sob o olhar de Paulo Freire - Waskievicz, Patricia (2020)
Considering that teaching practice requires a lot of knowledge to be constructed so that the child's education takes place in an integral and meaningful way, in this article, it is proposed to address some of this knowledge highlighted in legislation and literature. The objective is to clarify the specificity of the process of teaching children from 0 to 5 years of age, analyzing the educational practices proposed in the current legislation of Basic Education, in comparison with the pedagogical conception of Paulo Freire. The conclusion points to the importance of Freire's pedagogy as a potentializer of a comprehensive and motivating education for the child.